Factors Related to Lung Function In Wood Furniture Workers In Oesapa Village, Kelapa Lima Sub District Kupang City - Nabuasa, Diana Juniati; Berek, Noorce Ch; Setyobudi, Agus (Timorese Journal of Public Health, 2020)
Workers of wooden furniture is the workers who are at risk for decreased lung function caused by exposure to wood dust in the working environment. Wood dust will enter the respiratory organs, thereby affecting lung function. Decreased pulmonary function can be seen by the method of Harvard Step Test. This research aims to analyse the relationship between age, working period, nutritional status, smoking habits, long exposure to dust, and use of PPE with lung function in wooden furniture workers in Oesapa Village, Kelapa Lima Sub District, Kupang City. The study was analytic survey with Cross Sectional approach. This research was conducted in the wood furniture industry in Oesapa Vilage, Kelapa Lima District, Kupang City in July 2020. The population in this study was 33 workers of wooden furniture. Data collection is done by questionnaire, weight measurement, height measurement and the Harvard Step Test to determine the level of lung fitness workers. Data analysis technique used is the Chi Square test with level of significance . The results showed that there was a significant relationship between age (0.002), working period (0.023), nutritional status (0.039), and use of PPE (0.016) with lung function in workers of wooden furniture. There is no relationship smoking habits (0.093), long exposureto dust (0.057) and lung function in workers of wooden furniture.